Critical behavior of half-metallic ferromagnet Co3Sn2S2. (October 2018) - Yan, Weinian; Zhang, Xiao; Shi, Qi; Yu, Xiaoyun; Zhang, Zhiqing; Wang, Qi; Li, Si; Lei, Hechang
Abstract: We have investigated the critical behavior of a shandite-type half-metal ferromagnet Co3 Sn2 S2 . It exhibits a second-order paramagnetic-ferromagnetic phase transition with T C = 174 K. To investigate the nature of the magnetic phase transition, a detailed study of critical exponents has been carried out. The critical components determined from different analytical methods are consistent with each other and follow the scaling equation. It indicates that the exponents are unambiguous and intrinsic. Moreover, Co3 Sn2 S2 exhibits long-range magnetic interaction decaying as J ( r ) ∼ 1∕ r −( d + σ ) when σ = 1.28. Highlights: Report on the critical behaviors of Co3 Sn2 S2 is presented for the first time. Co3 Sn2 S2 is a half-metallic ferromagnet with second-order FM phase transition. The determined critical exponents of Co3 Sn2 S2 exhibit long-range FM interaction.